Prekurzory a vznik koloidního zákalu piva - Kotlíková, Blanka; Jelínek, Lukáš; Karabín, Marcel; Dostálek, Pavel (Chemické listy, 2013)
Colloidal haze is one of the most serious problems in modern brewing. The most common type of beer haze is formed from oligomeric polyphenols and proteins. The exact reaction mechanism of haze formation is not yet fully understood, though there are many theories dealing with this phenomenon. The best prevention of haze formation is to remove one or both the precursors. At present silica gels and polyamide sorbents are used for removing haze-active polyphenols.